Introduction to peptide science - Hamley, Ian W. (Hoboken, NJ : Wiley, 2020)
'The book covers the basic properties of peptides, essential synthesis methods, peptide aggregate structures including amyloid and other nanostructures such as peptide nanotubes and peptide gels. Then medically-related applications are considered in the last two chapters devoted to antimicrobial peptides and peptide therapeutics which are discussed in the context of peptide hormones, from which many of the most important peptide therapeutics introduced into practice (so far) are derived'--
Basic Properties -- Synthesis -- Amyloid and Other Peptide Aggregate Structures -- Antimicrobial and Cell-Penetrating Peptides -- Peptide Hormones and Peptide Therapeutics.
Includes bibliographical references and index.
Keywords: Peptides; Antimicrobial Cationic Peptides; Peptide Hormones; Nanotubes, Peptide